Persepsi Masyarakat tentang Keselamatan Pengguna Jalur Khusus Sepeda Motor di Jalan Raya Kota Denpasar - Indrawan, Anak Agung Bayu; Punia, I Nengah; Nugroho, Wahyu Budi (JURNAL ILMIAH SOSIOLOGI (SOROT), 2016)
ABSTARCT Traffic Jams is one of the urban problems that are inevitable in big cities in Indonesia. Denpasar city as the capital of Bali province also experienced problems of congestion and other transportation problems. The increasing number of people in Denpasar and the increasing mobility of society, leading to increased number of vehicles that have an impact on transportation matters. The number of motorcycles that dominate contributed the largest number of accidents. Management and traffic engineering must be done to reduce the number of accidents, one of them by creating a special line of motorcycles. This research explains how the public perception of a special line of motorcycles as well as the impact of its use on the safety of motorists. Social action theory put forward by Max Weber and the theory of social structuring Anthony Giddens with qualitative methods can explain the behavior of people in the Denpasar city driving in the special line of motorcycles. Basically any public behavior that is done consciously or unconsciously is the result of the action itself. Kata kunci: Â Persepsi, jalur khusus sepeda motor, perilaku masyarakat